2011
DOI: 10.1016/j.neuroscience.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Stress enhances muscle nociceptor activity in the rat

Abstract: Chronic widespread pain, such as observed in irritable bowel (IBS) and fibromyalgia (FMS) syndrome, are markedly affected by stress. While such forms of stress-induced hyperalgesia are generally considered manifestations of ‘central sensitization’, recent studies in patients with IBS and FMS suggest an additional, peripheral contribution. To examine the effect of stress on muscle nociceptor function, we evaluated activity in nociceptors innervating the gastrocnemius muscle in an animal model of chronic widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…18,47 Animals subjected to sleep disturbance 1 h daily for 10 consecutive days displayed mechanical and visceral hyperalgesia. 10,17,29 Consistently, the present study showed that REMSD 6 h daily for 4–5 consecutive days led to mechanical, thermal, and cold pain hypersensitivities in normal rats. These preclinical studies may mimic clinical observations, in which some patients with severe physical or psychological stress frequently report pain and exacerbated existing pain associated with chronic pain disorders.…”
Section: Discussionsupporting
confidence: 88%
“…18,47 Animals subjected to sleep disturbance 1 h daily for 10 consecutive days displayed mechanical and visceral hyperalgesia. 10,17,29 Consistently, the present study showed that REMSD 6 h daily for 4–5 consecutive days led to mechanical, thermal, and cold pain hypersensitivities in normal rats. These preclinical studies may mimic clinical observations, in which some patients with severe physical or psychological stress frequently report pain and exacerbated existing pain associated with chronic pain disorders.…”
Section: Discussionsupporting
confidence: 88%
“…Water-avoidance induced stress, which produces mechanical hyperalgesia, is considered a model of widespread muscle pain [29] is associated with increased firing in nociceptors innervating the gastrocnemius muscle [23]. To induce water avoidance stress, rats were placed on a 10 cm high acrylic platform (8 × 8 cm) in the center of a clear plastic tank (45 cm length × 25 cm width × 25 cm height) filled with room temperature tap water to a depth of 9 cm, for 1 h/day, for 10 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Visceral hyperalgesia (Bradesi et al, 2009(Bradesi et al, , 2007(Bradesi et al, , 2006He et al, 2013;Larauche et al, 2008 (Chen et al, 2011;Green et al, 2011b) Chapter 1…”
Section: Colorectal Distensionmentioning
confidence: 99%